ANALISIS DELIMITASI JENIS PADA Monascus Spp. MENGGUNAKAN SIDIK JARI DNA ARBITRARY PRIMER PCR - Nandang Suharna; Heddy Julistiono (Research Center for Biology-Indonesian Institute of Sciences, 2016)
A species delimitation analysis within Monascus spp. using Arbitrary Primer Polymerase Chain Reaction (AP PCR) DNA fingerprint was carried out. This is one of the methods used for identification and discrimination of bacterial strains within the same species. Its advantages including using single primer, independent of DNA quality, and observing amplicon shared by only some strain. This study analyzed Monascus sp. MM isolate which was originated from a source contaning high level of ethanol and two M. purpureus isolates which isolated from angkak. However, based on ITS region, 99% homology showed the unclear species delimitation. Therefore, this analysis was aimed at clarifying on the identities of Monascus species tested. The result showed DNA polymorphism among three isolates of Monascus that showed species delimitation. This study showed that species delimitation within Monascus isolates used in this analysis could be supported by AP PCR DNA fingerprinting. Therefor we suggested to use this technique or method for phylogenetic study to clarify taxonomic position of Monascus strains.